Early detection of hearing loss in tuberculosis patient using streptomycin by high frequency distortion product otoacoustic emissions (dpoae) and pure tone audiometry - Hazama, Mohamad (Pusat Pengajian Sains Perubatan, 2012)
Combination of Streptomycin, Isoniazid, Rifampicin and Pyrazinamide (SHRZ) are treatment of choice for tuberculosis. Streptomycin is known to cause ototoxicity, nephrotoxicity and neurotoxicity. Distortion product otoacoustic emission (DPOAE) is thought to be more sensitive for early detection of ototoxicity compare to pure tone audiometry (PTA). The aim of this study was to compare these two methods in newly diagnosed tuberculosis patients on streptomycin for early detection of ototoxicity. Ninety six newly diagnosed tuberculosis patients on streptomycin were screened and 50 patients finally included in this study. High frequency DPOAE and PTA were performed at several intervals. The incidence of ototoxicity in this study after completion two months ofiM Streptomycin (15 mglkg daily) is 29.2% (14 patients) using PTA (0.25- 8kHz). While using high frequency DPOAE detected ototoxicity in 77.1 % (37 patients). There was an association between ototoxicity with sex (P =0.011) and age ( P=0.003). There was no association between ototoxicity with other medications taken (P=0.621), pre treatment illness (P=0.140) and urea level (P=l.O). High Frequency (DPOAE) is a good monitoring tool for early detection of ototoxicity in tuberculosis patient on streptomycin compare to PTA.